Association between incidence of white matter hyperintensities in magnetic resonance imaging of the brain and smoking - Mijol, Mitchell Modi (2021)
Background: White matter hyperintensity (WMH) is a common finding on T2 weighted MRI brain or CT Brain among the older subjects. There has been a recognized linkage between the development of Dementia and Alzheimer's disease. Technological advancements in recent years have made the understanding of the pathogenesis of WMHs deeper, with several proposed mechanisms, focusing on anatomy, blood-brain barrier disruption, cerebral blood flow autoregulation, venous collagenases, and genetic factors. Smoking has been postulated to have an influence on WMH in several reports. Methods: A retrospective study was conducted in Hospital USM, Kota Bharu, Malaysia with MRI brain of patient aged 18 years and above were reviewed. The MRI must include both T2WI and FLAIR sequences. Patients with gross brain lesions, structural abnormalities, and history suggestive ongoing intracranial infection, inflammatory or demyelinating diseases were excluded. Demographic data regarding pack-years, age of initiation/cessation, duration of smoking, type of cigarettes (nonfiltered, filtered, e-cigarette) was collected and analysed using Pearson’s correlation method, Fisher exact test, and Independent T-test as necessary. Results: There was a significant association between age (p<0.001), smoking status (p<0.001) especially in the ex-smoker and passive smoker group (p=0.022), and comorbidities (p<0.001) with WMH. The mean age of participants in the WMH group was higher than No WMH (p<0.001). For smoking status, a higher prevalence of non smoker was found in the No WMH group. There was a high percentage of participants with no comorbidities reported to be in the No WMH group (n=80, 77.7%). Conclusion: Significant association was found between age, smoking status (Exsmoker and passive smoker), and co-morbidities with WMHs.